CLINICAL PROFILE AND MANAGEMENT OF HYPERTROPHIC SCARS AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL SURABAYA, INDONESIA - Perdanakusuma, Arda Rahmanisa; Iswinarno Doso Saputro; Evy Evrianti (Jurnal Rekonstruksi dan Estetik, 2024)
Highlights: Most hypertrophic scar patients were aged 17 to 25, mainly female, and the scars were mostly caused by burns on the face and upper extremities. Surgical techniques were the most common treatment, with most scars measuring 1 to 5 cm². Abstract:  Introduction: Scars is a prevalent clinical concern that is often more complex than commonly perceived. Hypertrophic and keloid scars results from atypical wound healing responses following trauma, characterized by an excessive deposition of connective tissue. In Indonesia, there are remains a paucity of data on the clinical profile and management of hypertrophic scars. To address this gap, researchers conducted a descriptive study to systematically examine various variables associated with hypertrophic scars, aiming to enhance understanding and inform more effective management strategies. Methods: This research is a retrospective descriptive analysis utilizing secondary data from medical records of patients with hypertrophic scars treated at Dr. Soetomo General Academic Hospital in Surabaya during the 2019 – 2020 period. The data were collected and processed according to key variables, including age, gender, occupation, etiology, anatomical location of the hypertrophic scars, scar size, and therapeutic interventions. Results:The number of patients with hypertrophic scars at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2019 to 2020 was 68. Most patients were aged 17 to 25 years. The gender distribution was nearly equal, with 50% male and 50.9% female patients. Among the patients, 12.5% and 43% were students. Burns caused 37.5% and 25% of cases. The most common scar locations were the face (25%) and upper extremities (25%). Most scars measured 1 to 5 cm² (25%). The most common treatment was surgical techniques (80% and 48%). Conclusion: Most hypertrophic scar patients were aged 17 to 25 years, predominantly female, and students. The primary cause of the scars was burns, with the scars most commonly located on the face and upper extremities. The majority of scars measured between 1 and 5 cm², and surgical techniques were the most widely used therapy.